BIOLOGY LESSON BY USING ANIMATION VIDEO’S MEDIA FOR SENIOR HIGH SCHOOL SYUDENTS - Yustika, Gaung Perwira (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2018)
The goal of giving Biology lesson at non formal course for senior high school students is for making them prepare on the school exams, enter university and as a important knowledge for the application functional of their daily life. Although biology is one of science subjects that everyday around us and in our daily environments, the students uninterested toward this subject, and having difficulties understanding biology lesson. Meanwhile, the writer found that a few of students take biology as an unimportant lesson at many reasons, one of them is more like another science subjects.The animation playing of videos was done at study course institute of Suhaymie Institute that located at seruni street number 51, Ketapang, Genteng, Surabaya, east Java. This activity ran at 2017/2018 academic calendar started from september 2017 to march 2018. The result showed all of students gave positive feedback 100% between 4 classes (alpha, beta, gamma, and delta) at the end of the lesson. The students became more understand about the lesson because video animation showed them audio-visually and the biological process can be seen directly.